The syntax and semantics of discourse markers - Urgelles-Coll, Miriam (Continuum studies in theoretical linguistics, 2010)
Offers a detailed overview of research on discourse markers covering different areas of linguistics: from a discourse analysis point of view, to a Relevance Theory perspective going through a computational linguistics approach. This book is of interest to researchers in semantics, pragmatics, grammar and discourse analysis